Dynamics of Gene Expression of Pro- and Antiangiogenic Factors at the Background of Application of Cord Blood Nucleated Cells in Experimental Model of Neovascular Retinopathy - Beletskaya, Polina V.; Demin, Yuriy A. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Â  Probl Cryobiol Cryomed 2014; 24(2):166.